Civilian Use of Unmanned Aerial Vehicles (UAV) and Threat to Data Privacy - Alizada , Sh.S. (Herald of Azerbaijan Engineering Academy, 2023)
The article examines the inherent benefits of civilian use of unmanned aerial vehicles (UAVs) and the possible violation of fundamental rights such as the right to privacy and freedom of expression. The article describes the possibility of using UAVs at the data collection stage using the example of Israeli law as a basis for overcoming the risks associated with the use of UAVs. Israel is considered the leading manufacturer of UAVs, and therefore the integration of the Israeli legal system into both common and civil law is attracting attention today. The article also discusses the solution of such problems adopted in the USA and Europe.